Results of an interactively coupled atmospheric chemistry – general circulation model: Comparison with observations - R. Hein; M. Dameris; C. Schnadt; C. Land; C. Land; V. Grewe; I. Köhler; M. Ponater; R. Sausen; B. B. Steil; J. Landgraf; J. Landgraf; et al. (Annales Geophysicae, 2001)
The coupled climate-chemistry model ECHAM4.L39(DLR)/CHEM is presented which enables a simultaneous treatment of meteorology and atmospheric chemistry and their feedbacks. This is the first model which interactively combines a general circulation model with a chemical model, employing most of the important reactions and species necessary to describe the stratospheric and upper tropospheric ozone chemistry, and which is computationally fast enough to allow long-term integrations with currently available computer resources. This is possible as the model time-step used for the chemistry can be chosen as large as the integration time-step for the dynamics. Vertically the atmosphere is discretized by 39 levels from the surface up to the top layer which is centred at 10 hPa, with a relatively high vertical resolution of approximately 700 m near the extra-tropical tropopause. We present the results of a control simulation representing recent conditions (1990) and compare it to available observations. The focus is on investigations of stratospheric dynamics and chemistry relevant to describe the stratospheric ozone layer. ECHAM4.L39(DLR)/CHEM reproduces main features of stratospheric dynamics in the arctic vortex region, including stratospheric warming events. This constitutes a major improvement compared to earlier model versions. However, apparent shortcomings in Antarctic circulation and temperatures persist. The seasonal and interannual variability of the ozone layer is simulated in accordance with observations. Activation and deactivation of chlorine in the polar stratospheric vortices and their inter-hemispheric differences are reproduced. Considering methane oxidation as part of the dynamic-chemistry feedback results in an improved representation of the spatial distribution of stratospheric water vapour concentrations. The current model constitutes a powerful tool to investigate, for instance, the combined direct and indirect effects of anthropogenic trace gas emissions. Key words. Atmospheric composition and structure (middle atmosphere – composition and chemistry) – Meteorology and atmospheric dynamics (general circulation; middle atmosphere dynamics)